The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf01066419
|View full text |Cite
|
Sign up to set email alerts
|

Receptor inhibition by immunoglobulins: Specific inhibition by autistic children, their relatives, and control subjects

Abstract: Forty-two parents of children with autistic disorder, 15 children with autistic disorder, 17 siblings of children with autistic disorder, and 12 unrelated normal adult controls were studied to determine if immunoglobulins isolated from their plasma would inhibit binding of the 5HT1A agonist, [3H]-8-hydroxy-N,N-dipropyl-2-aminotetralin (DPAT) to 5HT1A receptors in human hippocampal membranes. There were no significant differences among the means of percentage inhibition of DPAT binding of parents, children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Some authors have suggested that individuals with autism and regression might represent a distinct PDD subtype (Rogers 2004). It has also been hypothesised that regression might follow specific environmental triggers (Kurita 1985;Cook et al 1993;Warren et al 1996;van Gent et al 1997). The possibility of 'environmentally mediated' regression has been investigated indirectly by measuring the rate of autism related milder phenotypes (the broader autism phenotype) amongst the parents of children with autism with and without regression.…”
Section: Introductionmentioning
confidence: 97%
“…Some authors have suggested that individuals with autism and regression might represent a distinct PDD subtype (Rogers 2004). It has also been hypothesised that regression might follow specific environmental triggers (Kurita 1985;Cook et al 1993;Warren et al 1996;van Gent et al 1997). The possibility of 'environmentally mediated' regression has been investigated indirectly by measuring the rate of autism related milder phenotypes (the broader autism phenotype) amongst the parents of children with autism with and without regression.…”
Section: Introductionmentioning
confidence: 97%
“…This could be compatible with a compensatory increase in serotonin production, explaining the increased levels in blood. It has been suggested that antibodies to serotonin receptors may be characteristic of some children with autism, but Cook et al [1993] presented data discounting that theory. Apter et al [1991] have reviewed the research on tryptophan (the dietary precursor of serotonin) in relation to autistic disorder.…”
mentioning
confidence: 83%
“…Viral infection, or the immune response to viral infection, has been proposed to result in antibody production to neurotransmitter receptors such as serotonin binding sites [Todd and Ciaranello, 1985;Singh et al, 1997]. The possibility of immunoreactivity at serotonin binding sites is controversial [Yuwiler et al, 1992;Cook et al, 1993]. Prenatal exposures that might alter brain development by immunologic mechanisms have also been proposed.…”
Section: Evidence For Neuroimmune Insult In Asdmentioning
confidence: 97%